Il faut sauver l’auditeur Matías Delgado y Florez. Lettre d’un magistrat de Manille du 30 novembre 1631, à son frère Sancho, à Cáceres - Guillaume Gaudin (Diasporas: Circulations, Migrations, Histoire)
The letter of Manilla magistrate Delgado y Florez to his brother Sancho who remained in Spain is rare because we seldomly have private writings of officers in the Hispanic Monarchy. On the one hand, the letter tells about the barrier of distance in communications between the different parts of the Spanish Empire. On the other hand, it shows the different circles of Delgado’s social relations from relatives accompanying him in the Philippines, to members of his family in Spain and to powerful figures of the Court. Finally, the letter focuses on the experiences and feelings of a senior Spanish judge who considered himself a recluse at the end of the world, in the Philippine archipelago in distant Asia.